THE INFLUENCE OF QUALITY OF WORK LIFE (QWL) AND EMPLOYEE ENGAGEMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) OF DALMAS MEMBERS OF DITSAMAPTA POLDA DIY WITH RESISTANCE TO CHANGE AS A MODERATING VARIABLE - Lukman Dwi Rismanto; Kusuma Chandra Kirana; Didik Subiyanto (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The objective of this research is to investigate how Employee Engagement impacts Organizational Citizenship Behavior (OCB) with Resistance to Change as a moderating factor among DIY POLDA personnel. The study utilizes a quantitative method with Structural Equation Modeling (SEM) for analysis. Participants were selected through purposive sampling, focusing on Dalmas Ditsamapta DIY POLDA personnel who are at least 18 years old. Data were collected through a Likert scale-based questionnaire and analyzed using WarpPLS version 8. The results showed that: (1) Quality of Work Life (QWL) has a significant effect on OCB, where a comfortable and supportive work environment can increase personnel's voluntary work behavior, including willingness to work overtime. (2) Employee Engagement does not have a significant effect on OCB, which indicates that the company's lack of communication and involvement with personnel leads to low appreciation and work motivation. (3) Resistance to Change is shown to moderate the relationship between QWL, Employee Engagement, and OCB. Personnel facing new regulations often feel anxious and are encouraged to improve skills through collaboration between team members. This research provides a theoretical contribution in enriching the study of OCB, especially in police institutions. Suggestions include the importance of increasing personnel engagement and building a supportive work environment, so as to create more positive work behavior. Further research is expected to use different variables and analysis methods to broaden insights into the factors that influence OCB.